PENGGUNAAN FACEBOOK SEBAGAI MEDIA PEMASARAN ONLINE - CAHYONO, DARMAWAN BUDI (Kajian Ilmiah Mahasiswa Manajemen, 2013)
Businessmen claimed to be easier to market its products through facebook as the first target of this business is known, making it easy to communicate with. Facebook marketing is not just a matter of promotion but there is a lot of value contained in it. The purpose of Facebook marketing is to build community, to create a series of connected, creating communication, credibility, sell, mendaangkan visitors. There are four advantages in doing Facebook marketing activities, namely: the cost of a cheap promotion, making friends while promotions targeted market, target, and Facebook marketing is suitable for building credibility and branding. Facebook Marketing has the following advantages: the Internet boom, including Facebook most visited website, Facebook provides information, Facebook provides a column to fill a variety of information the wearer, the focus of market segmentation, easily accessible, easy to communicate, there is zero time feedback, always connected, Low budget, high impact, and New wave marketing